Thrombolytic Activity and Protein Characterization of Extract from White Oyster Mushroom (Pleurotus ostreatus) - Alishlah, Tanfidz; Umayah Ulfa, Evi; Arimurti, Sattya; Eka Putri, Khilwiyah (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2025)
Venous thromboembolism (VTE) is a condition resulting from the presence of thrombi within blood vessels. Globally, these illnesses are the leading causes of death. In 2022, the WHO estimates that 19.8 million fatalities or 32% of worldwide deaths were a result of cardiovascular disease, which is initiated by thromboembolism. The use of thrombolytic medicines is one treatment option for thromboembolic illness. The exploration revealed that numerous mushrooms contain protease enzymes with a thrombolytic effect. A common edible mushroom in Indonesia is the white oyster mushroom (Pleurotus ostreatus). By assessing thrombolytic activity using the Blood Clot Lysis Assay method and characterizing proteins using SDS-PAGE electrophoresis, this study aims to determine the thrombolytic activity of the extract and crude protein from the white oyster mushroom. The findings demonstrated the thrombolytic activity of the extract and crude protein of oyster mushroom at 29.89% and 37.89%, respectively. The extracts with volumes of 500 µl and the crude protein with a concentration of 0.05 g/mL exhibited the highest thrombolytic activity. The thrombolytic activity results of the extract (500 µl) and crude proteins (0.02 g/mL and 0.05 g/mL) of the white oyster mushroom were significantly higher than the positive control (p<0.05). According to protein characterization, the white oyster mushroom extract and crude protein had protein molecular weights of 45.50 kDa, 32.51 kDa, 21.09 kDa, and 15.1 kDa, respectively. White oyster mushroom extracts and crude protein have the potential to be developed as thrombolytic agents, serving as a safe, natural, and cost-effective alternative for thromboembolism disorders. While the results offer an important foundation, further studies are necessary to confirm and extend these findings.